NEW SPECIMENS OF MERYCOPOTAMUS (ARTIODACTYLA: ANTHRACOTHERIIDAE) FROM MIDDLE MIOCENE OF POTWAR PLATEAU, PAKISTAN - M. Asim; K. Aftab; M. K. Nawaz; M. A. Khan; M. A. Babar; S. G. Abbas; M. Hussain; M. Akhtar; A. M. Qureshi (Journal of Animal and Plant Sciences, 2020)
The Merycopotamus remains are described from the Chinji Formation (middle Miocene) of the Lower Siwalik Subgroup of Pakistan. The material recovered from two fossiliferous localities of Chabbar Syedan and Dhok Bun Ameer Khatoon in Chakwal district, Punjab, Pakistan. The described specimens of Merycopotamusnanus add additional knowledge on Pakistani anthracotheriid diversity.
Keywords: Artiodactyls; Anthracotheriids; Merycopotamus; Chinji Formation; middle Miocene